Hypothermic Oxygenated Machine Perfusion Reduces Early Allograft Injury and Improves Post-transplant Outcomes in Extended Criteria Donation Liver Transplantation From Donation After Brain Death: Results From a Multicenter Randomized Controlled Trial (HOPE ECD-DBD). Issue 5 (29th November 2021) - Czigany, Zoltan; Pratschke, Johann; Froněk, Jiří; Guba, Markus; Schöning, Wenzel; Raptis, Dimitri Aristotle; Andrassy, Joachim; Kramer, Matthijs; Strnad, Pavel; Tolba, Rene Hany; Liu, Wenjia; Keller, Theresa; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to evaluate peak serum alanine aminotransferase (ALT) and postoperative clinical outcomes after hypothermic oxygenated machine perfusion (HOPE) versus static cold storage (SCS) in extended criteria donation (ECD) liver transplantation (LT) from donation after brain death (DBD). Background: HOPE might improve outcomes in LT, particularly in high-risk settings such as ECD organs after DBD, but this hypothesis has not yet been tested in a randomized controlled clinical trial (RCT). Methods: Between September 2017 and September 2020, 46 patients undergoing ECD-DBD LT from four centers were randomly assigned to HOPE (n = 23) or SCS (n = 23). Peak-ALT levels within 7 days following LT constituted the primary endpoint. Secondary endpoints included incidence of postoperative complications [Clavien-Dindo classification (CD), Comprehensive Complication Index (CCI)], length of intensive care- (ICU) and hospital-stay, and incidence of early allograft dysfunction (EAD). Results: Demographics were equally distributed between both groups [donor age: 72 (IQR: 59–78) years, recipient age: 62 (IQR: 55–65) years, labMELD: 15 (IQR: 9–25), 38 male and 8 female recipients]. HOPE resulted in a 47% decrease in serum peak ALT [418 (IQR: 221–828) vs 796 (IQR: 477–1195) IU/L, P = 0.030], a significant reduction in 90-day complications [44% vs 74% CD grade ≥3, P = 0.036; 32 (IQR: 12–56) vs 52 (IQR: 35–98) CCI, P = 0.021], and shorter ICU- and hospital-stays [5 (IQR: 4–8) vs 8 (IQR: 5–18) days, P = 0.045; 20 (IQR: 16–27) vs 36 (IQR: 23–62) days, P = 0.002] compared to SCS. A trend toward reduced EAD was observed for HOPE (17% vs 35%; P = 0.314). Conclusion: This multicenter RCT demonstrates that HOPE, in comparison to SCS, significantly reduces early allograft injury and improves post-transplant outcomes in ECD-DBD liver transplantation.